(untitled) (Research, Society and Development, 2024)
Anaphylactic shock is a severe and potentially fatal allergic reaction that requires immediate intervention. This literature review aims to analyze the management strategies for anaphylactic shock in the emergency department, emphasizing the importance of early administration of epinephrine, airway maintenance, and intravenous fluid administration. The research was conducted in the databases Google Scholar, LILACS, and SCIELO, covering publications from 2000 to 2024 in Portuguese, English, and Spanish. The results indicate that the lack of knowledge and adequate training among healthcare professionals can delay treatment, exacerbating the severity of the condition. Furthermore, the review highlights the need for standardized protocols and continuous education of healthcare professionals to improve patient outcomes. Patient education and prevention of future reactions are critical components of anaphylactic shock management, underscoring the importance of preventive strategies and long-term follow-up.